Conservation and improvement of native chicken: performance of fourth generation (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
Study was conducted at Bangladesh Livestock Research Institute, Savar, Dhaka with the objectives (i) to assess the performances of three Indigenous Chicken genotypes under intensive management, (ii) to select parental birds (males and females) and breed them in an assortative design   for the production of fourth generation birds, and (iii) to estimate realized responses to selection to improve 3 Indigenous Chicken genotypes. A total of 1050-day-old chicks comprising of 3 types of chicken namely Naked Neck (NN), Hilly (H) and Non-descript Deshi (ND) were hatched in one batch for this study. In fourth generation (G4), selection was practiced at 40-week of age on the basis of an index comprising the parameters of age at first egg (AFE), body weight (BW), egg production (EP) and egg weight (EW). Improvement target of egg weight was to increase by 1g, egg production rate was to increase by 2 % per generation. The data were analyzed by factorial arrangement in a CRD by General Linear Model (GLM) Univariate Procedure in SPSS Computer Program. Day old chick weight was significantly (p